2020
DOI: 10.1038/s41598-020-77627-5
|View full text |Cite
|
Sign up to set email alerts
|

Children’s coordination of the “sweet spot” when striking a forehand is shaped by the equipment used

Abstract: Children’s movement coordination is significantly influenced by the equipment used when performing multi-articular actions. Previously we reported that scaled equipment (smaller racket and a softer ball), but not full-sized equipment, promoted a functional coupling between upper arm and forearm angles in children performing a forehand. However, it remains unclear whether the shoulder-racket distance—which is controlled by this coupling—is a performance variable. This study therefore advanced previous research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…Reliable results were also obtained in technical training, except for stuffing the ball with a racket without bouncing off the floor p>0.05. Conclusions: using the presented complexes of specially selected exercises positively influenced the changes in physical and technical fitness indicators, which allows recommending 6-7-year-old Buszard, T., Garofolini, A,, Whiteside, D., Farrow, D., & Reid, M. (2020) [Slobozhanskyi herald scientific and sports], no 4(54), 47-52. doi: 10.15391/snsv.2016-4.014 [in Russian].…”
Section: вступmentioning
confidence: 92%
See 1 more Smart Citation
“…Reliable results were also obtained in technical training, except for stuffing the ball with a racket without bouncing off the floor p>0.05. Conclusions: using the presented complexes of specially selected exercises positively influenced the changes in physical and technical fitness indicators, which allows recommending 6-7-year-old Buszard, T., Garofolini, A,, Whiteside, D., Farrow, D., & Reid, M. (2020) [Slobozhanskyi herald scientific and sports], no 4(54), 47-52. doi: 10.15391/snsv.2016-4.014 [in Russian].…”
Section: вступmentioning
confidence: 92%
“…Отримані результати підтверджують дослідженнями комплексного використання спеціально підібраних вправ в тренувальному процесі початкового етапу підготовки (Shevchenko, & et al, 2021) Напрями візуального контролю за виконанням та удосконалення техніки ударів тенісистів висвітлені в працях Buszard T. із співавторами (Buszard, & et al, 2020). Автори (Penalva, & et al, 2022) Abstract.…”
Section: вступunclassified
“…This implies that anticipatory skill might also emerge in youth sport if the game is modified appropriately. For example, modifying tennis by means of using scaled rackets, lower compression balls, lower nets and/or smaller courts has manifested in a number of desirable changes, including more aggressive strokeplay (e.g., faster rallies, more winners without an increase in errors, more approaches to the net, and more shots struck inside the baseline) [60][61][62], fewer errors [63], superior serving [61,64,65], and improved coordination [66,67]. Similar results were evident when cricket was modified, with a shorter pitch leading to perception-action coupling more akin to professional cricket (i.e., short-pitched deliveries were played off the back foot rather than the front foot) [68], more accurate bowling, which also leads to batters having more opportunities to strike the ball [69,70], and bowling with a technique that is deemed at less risk of injury [71].…”
Section: Temporal Pressure and The Youth Sport Environmentmentioning
confidence: 99%
“…In outstanding works, Buszard et al, (2020a,b) showed that a scaled racket (21 inches) and low compression balls promoted functional movement variability, whereas standard, full-size racket (27 inches) and balls resulted in the freezing of mechanical degrees of freedom during a forehand stroke task performed by beginner children (Buszard et al, 2020a). They also reported that scaled equipment promoting a more distal control of the shoulder-racket distance than full-sized equipment (Buszard et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%